(untitled) (diségno, 2021)
The extraordinary endeavour of William Kentridge is the testimony of an intense, many years and productive work that relates to the dynamics of a complexity located in the cultural and political context of belonging, so being able to interpret it means being confronted with a visual universe capable of reflecting a precise personal need, in privileging the medium of drawing and in the freedom to hybridize it with cinema and theatre (read more).